PELAYANAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR MELALUI E-COMMERCE MENUJU GOOD GOVERNANCE - Helmi Azahari (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to find out how e-commerce is a tool to improve public services, especially for motor vehicle tax payments. The essence of innovation to serve the public is how to provide improved services to the public according to advances in information technology. Previous research related to public services has revealed more about the analysis of public services (Rinaldi, 2012) or public service innovations (Hartomi et al, 2018). However, this study aims to determine whether the payment of motor vehicle taxes through e-commerce is included as an effort to provide good public services to achieve good governance. According to the theory of public service management, what is called good governance must meet the needs of the community for public services, namely participation, rule of law, transparency, responsiveness, orientation to consensus, equality, effective and efficient operation, accountability and strategic vision. This research uses a qualitative method with a case study approach. The results show that the motor vehicle tax payment service through Bukalapak in the Bekasi City area, West Java, has met most of the criteria to serve the public well.Keywords: Good Governance, Public Services, PKB Payments at E-Samsat